Rheological Properties, Textural Properties and Storage Stability of Sauce Enriched with Pomace from Oxheart Tomatoes (Lycopersicon esculentum) - Dumitrița Flaiș; Mircea Oroian (Foods)
The objective of this study was to develop a novel sauce formulation in which egg yolk was substituted with pea and soy proteins, in addition to the incorporation of tomato pomace as a functional ingredient. Nine experimental samples (E1–E3, S1–S3, and P1–P3) and three control samples (E0, S0, and P0) were prepared, corresponding to three protein sources (E: egg yolk, S: soy, P: pea), with increasing concentrations of tomato pomace (0, 2, 4, and 6%). The formulations were adjusted proportionally in terms of water and oil to maintain the desired consistency. The analyses performed included: physico-chemical analysis of the sauce (fat content, peroxide value, and CIE L* a* b* color determination), quality assessment using Fourier Transform Infrared Spectroscopy (FT-IR, rheological measurements, and microstructural evaluation. The sample designated P2 demonstrated a notable correlation with favourable parameters, exhibiting intense colouration, elevated protein content, and consistent rheological properties. However, at higher levels of tomato pomace (notably 6%), microstructural instability was observed, which may limit the formulation’s robustness over time. These findings demonstrate that tomato pomace can enhance the functional and structural characteristics of sauce, while also highlighting the importance of optimizing concentration levels to avoid negative impacts on emulsion stability. Overall, the results support the use of tomato pomace and plant proteins in the formulation of sustainable and innovative food products.